Bifunctional Intimacy and its Interplay with Metal‐Acid Balance in Shaped Hydroisomerization Catalysts. Issue 18 (11th August 2020) - Mendes, Pedro S. F.; Silva, João M.; Ribeiro, M. Filipa; Daudin, Antoine; Bouchy, Christophe
Abstract: The combined impact of platinum location and metal‐acid balance on the catalytic performances of HUSY zeolite alumina‐shaped bifunctional catalysts was evaluated in n ‐hexadecane hydroconversion reaction. For well‐balanced catalysts, the deposition of Pt in the alumina resulted in lower isomerization selectivity as compared to when platinum was located in the zeolite. In the latter case, the maximal distance between Pt and acid sites was found to be in the nanometric scale (high intimacy) whereas in the former it was in the micrometric scale (low intimacy), particularly due to the presence of large clusters of HUSY zeolite. Nevertheless, whenever proper balance between functions was not ensured in high‐intimacy catalysts, the low‐intimacy and well‐balanced catalysts were shown to perform better. The requirement for nanometric metal‐acid sites intimacy must be hence combined with an adequate metal‐acid balance to achieve optimal catalytic performance. Abstract : A matter of metal‐acid intimacy and balance : Design of efficient hydroisomerization catalysts is crucial to the sustainable production of liquid fuels, but the bifunctional character of the catalyst introduces additional complexity. To unravel this complexity, the interplay between the intimacy and balance of metal‐acid sites was investigated over industrially‐relevant shaped catalysts.